Assessment of heavy metal contamination in the atmospheric deposition during 1950–2016 A.D. from a snow pit at Dome A, East Antarctica. (1st January 2021) - Liu, Ke; Hou, Shugui; Wu, Shuangye; Zhang, Wangbin; Zou, Xiang; Yu, Jinhai; Song, Jing; Sun, Xuechun; Huang, Renhui; Pang, Hongxi; Wang, Jiajia
Abstract: Antarctic trace element records could provide important insights into the impact of human activities on the environment over the past few centuries. In this study, we investigated the atmospheric concentrations of 14 representative heavy metals (Al, As, Cd, Co, Cu, Fe, K, Mg, Mn, Pb, Sb, Sr, Tl and V) from 174 samples collected in a 4-m snow pit at Dome Argus (Dome A) on the East Antarctic Plateau, covering the period from 1950 to 2016 A.D. We found great variability in the annual concentration of all metals. The crustal enrichment factors suggest that the concentrations of some heavy metals (Cd, Sb, Cu, As and Pb) were likely influenced by anthropogenic activities in recent decades. An analysis of source regions suggests that heavy metal pollution at Dome A was largely caused by human activities in Australia and South America (e.g. mining production, leaded gasoline). Based on the relationship between the trace elements fluxes and sea ice concentration (SIC), sea surface temperature (SST) and annual mean air temperature at 2 m above the ground (T2m ), our analysis shows that deposition and transport of atmospheric aerosol at Dome A were influenced by circum-Antarctic atmospheric circulations. Graphical abstract: Image 1 Highlights: First high-resolution trace elements were determined at Dome A, on the East Antarctic Plateau. Anthropogenic elements (Cd, Sb, Cu, As and Pb) likely come from South America. Element fluxes are affected by sea ice, sea surface and air temperature.